Systematic literature review : Overview of the implementation of interactive multimedia on learning outcomes in mathematics learning - Sutomo, Woro Anglia Banda; Turmudi (Journal Focus Action of Research Mathematic (Factor M), 2024)
Multimedia interaktif telah menjadi sarana efektif dalam media pembelajaran. Dalam mata pelajaran matematika, multimedia interaktif dapat memberikan kontribusi untuk meningkatkan pemahaman yang berkaitan dengan hasil belajar matematika. Melibatkan elemen – elemen multimedia seperi animasi, suara, video dan simulasi dapat membuat siswa ikut andil dalam menggambarkan konsep - konsep matematika dengan cara yang lebih visual dan dinamis. Akan tetapi, pendidikan matematika di Indonesia masih terbatas dalam menggunakan multimedia interaktif, sehingga peneliti ingin mengidentifikasi dan memberikan gambaran yang luas tentang penggunaan multimedia interaktif terhadap hasil belajar siswa dalam pembelajaran matematika. Metode penelitian yang dipilih dalam penelitian ini adalah Systematic Literature Review.Studi primer yang digunakan yaitu artikel yang dipublikasikan periode 2019-2023. Berdasarkan penelitian ini ditemukan bahwa terdapat 188 artikel mengenai penggunaan multimedia interaktif terhadap hasil belajar matematika pada semua jenjang pendidikan dengan 4 jenis multimedia interaktif. Ditemukan artikel yang berindeks Sinta X merupakan artikel terbanyak dalam publikasi dengan demografi penelitian tertinggi di Pulau Jawa. Penelitian dengan metode Research and Development merupakan penelitian yang paling banyak ditemukan.   Interactive multimedia has become an effective means of learning media. Interactive multimedia in mathematics learning can contribute to increasing understanding related to mathematics learning outcomes. Involving multimedia elements such as animation, sound, video and simulations can make students take part in depicting mathematical concepts in a more visual and dynamic way. However, mathematics education in Indonesia is still limited in using interactive multimedia, so researchers want to identify and provide a broad picture of the use of interactive multimedia on student learning outcomes in mathematics learning. The research method chosen in this research is Systematic Literature Review. This research aims to systematically present and analyze relevant literature that has been published on this topic. The primary study used is articles published in the 2019-2023 period. Based on this research, it was found that there were 188 articles regarding the use of interactive multimedia on mathematics learning outcomes at all levels of education with 4 types of interactive multimedia. It was found that articles with the Sinta X index were the most articles in publications with the highest research demographics on the island of Java. Research using the Research and Development method is the research that is most often found